MODEL PEMBELAJARAN PROBLEM BASED LEARNING DISERTAI VIDEO STOP MOTION PADA MATERI IPA SMP - Ratiwi Arianti (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
The most junior high school students will find it difficult to explore material if only by lecture method, especially difficult to understand science materials. Because the lecture method is very minimal to get a response from students, as a result the sense of interest in students will decrease. In addition the lecture method also cannot make students think critically, while along with the advancement of education and curriculum students are required to be able to think critically. Then the Problem Based Learning learning model is a model that will teach and make students think critically through existing problems. Video is a tool that can increase students' interest in learning. Stop motion video is one video that can attract students' attention because there are uniquepictures that can be made by the instructor themselves, of course this will be easily understood by students. This study aims to apply the stop motion video in the Problem Based Learning (PBL) learning model to improve students' understanding and make students think critically. This type of research is a literature study. In this literature study we will look for some of the literature related to this research. The literature used is several things that contain the application of the PBL model using video. Keywords:Problem Based Learning, learning media, Stop Motion